Students’ Problems in Writing Academic Article: A Case Study in Academic Writing Class - Maharani, Ramanda; Hakiki, Shabrina Shalihatinisa; Safitri, Suci (English Education: Jurnal Tadris Bahasa Inggris, 2023)
This research was conducted to find students’ problems in writing academic articles. The participants were 36 students in Academic Writing Class. The authors used a questionnaire and an interview to gain the data. The results of this study were explained by descriptive analysis. The data shows that students experience problems while writing an article. The main problems are lack of knowledge (organization, vocabulary, and grammar) and motivation. Furthermore, students also experience anxiety during the article-writing process.